Influence of laser pulse shape and cleanliness on two-photon microscopy - Chong, Shau Poh (2024)
Nonlinear microscopy, including two-photon microscopy, requires pulsed lasers as light source. Typically, when choosing the appropriate pulsed laser for two-photon microscopy, the pulse repetition rate, pulse width, total power output, and output beam diameter are among the critical parameters which are often emphasised. Here, we demonstrate that the pulse shape, often overlooked, can have significant impact on the two-photon microscopy excitation efficiency and the effective signal brightness. We provide metrics to ease practical selection of pulsed laser sources for two-photon microscopy.